Synergistic effect of proteins and tannic acid-yielding systems with improved mechanical performance for use in load-bearing tissues - Maria Clara Gomes; Claudio Mortier; Håvard J Haugen; Jonny J Blaker; João F Mano (Materials Research Express)
Developing bioactive hydrogels with mechanical properties resembling those of load-bearing connective tissues remains a significant challenge in the biomedical field. In this study, we address this limitation by incorporating human platelet lysate (PL) proteins, tannic acid (TA), and chitosan methacrylate (CHI-MA) to formulate reinforced hydrogel systems with markedly improved mechanical performance. The resulting PL/CHI-MA/TA hydrogels exhibit exceptional mechanical characteristics, attaining strengths of approximately 7 MPa and stiffness values of 5 MPa, comparable to those found in load-bearing tissues such as cartilage. This improvement can be attributed to the synergistic effect, which enhances the interaction between PL proteins and the polymeric network, thereby increasing strength, toughness, and efficient energy dissipation. Moreover, these hydrogels support the adhesion and proliferation of human-derived adipose stem cells, underscoring their potential utility in tissue engineering and regenerative medicine applications targeting load-bearing connective tissues, such as cartilage.